The Coronavirus Disease 2019 Outbreak Highlights the Importance of Sex-sensitive Medicine - Angela HEM Maas; Sabine Oertelt-Prigione (European Cardiology Review)
The novel coronavirus disease 2019 (COVID-19) pandemic has revealed important differences between the sexes in epidemiology, risk factors, clinical course, mortality and socioeconomic dimensions of the disease in all populations worldwide. This has emphasised the need for a better understanding of diversity aspects in healthcare to improve prevention, treatment and long-term consequences. In this article, the authors describe the most relevant knowledge thus far on sex differences regarding COVID-19.